The Digital animation as a device for capturing images: The subjective relationship between digital animation and the audiovisual experience in animated documentary - Souza, Natacha de; Torres, David Ruiz (Farol, 2024)
The animated documentary, a form of cinema that uses digital animation to tell intimate and engaging stories, has been gaining prominence at film festivals and winning awards. Works such as Flee (2021) by Jonas Rasmussen and Waltz with Bashir (2008) by Ari Folman exemplify this recent trend, exploring personal stories and remarkable events through animation. These films are just a few examples of how animated documentaries are redefining the contemporary audiovisual scene, mixing two languages that until then didn't seem to communicate very well and stimulating reflections on the concepts of documentary and animation in relation to the representation of reality.
Keywords: Digital animation.; Animated documentary.; Visual device.; Digital technology.; Hybrid cinema.